The potential of efficient water management system in high-rise design - Hee, A.B; M.M. Tahir,; Abdul Halim Ismail,; M.F. Bukhori, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Water is a natural gift upon all life forms since the early civilization of mankind and Malaysia is one of the nation that is rich with water resources. Since decades ago, the development in the water sector spurs the social economic growth of this country (Mohd. Azhar, 2000). As time goes by with rapid urbanisation across Malaysia, the demand for water especially in buildings, increase to accommodate a growing population and their needs. Roodman et al. (1995) and the United Nations Environment Programme (UNEP) (Al-Tamimi, 2011) highlight that the World watch Institute estimates building consumption to be at least 40% of the world’s energy and 16% of the water used annually. However, issues like increasing wastages and mismanagement of water leads to a problem towards this resources. Hence, the first part of the paper assesses the issues faced globally and locally towards water resources and the principles of water quality cascade in relation to sustainable water management in buildings. The next part are collective reviews of two selected case studies that include sustainable water management in the respective building design approach. The significant of this paper is to encourage the mind set of designers to contemplate and develop a more efficient water management system in high-rise buildings design as well as the importance for regulatory authorities and consultants to integrate the principles of sustainable water management onto development governing.